Knowledge, attitudes and practices of HIV post-exposure prophylaxis among Registrars at the University of the Witwatersrand - Nkandlalalana, Sipho (My University, 2022)
Introduction: According to the World Health Organization (WHO), 90% of occupational, percutaneous exposure to blood borne infections occur in developing countries. Doctors under training are highly susceptible to occupational hazards such as needle stick injuries. HIV Post-Exposure Prophylaxis (PEP) refers to administering antiretroviral drugs as an emergency measure after exposure to HIV infection to reduce its acquisition. This study assessed the knowledge, attitudes and practices of HIV PEP among registrars in all disciplines at the University of the Witwatersrand in South Africa. Methods: In this cross-sectional study, a structured questionnaire with self-administered questions was used. Convenience sampling was used to select first to final year registrars across all clinical specialities within the University of the Witwatersrand. Results: The majority (87.7%) of the respondents had an above average knowledge of HIV PEP and the difference in knowledge scores across the years was not statistically significant. Participants in the study showed a positive attitude towards HIV PEP. The majority (91%) of the registrars, who were exposed, took PEP. Of those, 74.2% completed the prescribed duration of 28 days. Conclusion: In this study, there was an association between above average knowledge, a positive attitude towards HIV PEP and there were good practices of HIV PEP among registrars.
A research report submitted in fulfilment of the requirements for the degree of Masters of Medicine in Internal Medicine to the Faculty of Health Sciences, School of Clinical Medicine, University of the Witwatersrand, Johannesburg, 2021